Implementation of an emergency medical programme in Wielkopolska Province - Gaca, Michał; Witkowski, Artur (Przewodnik Lekarza/Guide for GPs, 2007)
Among the goals of present day man is to pursue the aim of preserving life and health for as long as possible. One method to achieve this is to reduce mortality related to injuries and acute diseases. This can be obtained, for all, by creating an efficient emergency system in sudden life and health threatening events, i.e. an emergency medical system. The aim of this paper is to analyze the process of creating this system in Wielkopolska Province between 1999 and 2005 and to present its condition at the end of 2005. The research methodology has included the analysis of hitherto unpublished documents and primary texts. The research has proved that between 1999 and 2005 an emergency medical system was created in Wielkopolska Province before its legislative was developed. At the end of 2005 there were as many as twenty-four emergency departments, one hundred emergency ambulances, and twelve emergency call centres. When assessing the functioning of these units we cannot consider them as a unified system but only as its elements operating in the Province. The advantage of administrative division over operating regions of emergency departments makes this system work less efficiently in many areas of the Province. On the basis of the conclusions of the paper it has been suggested that the emergency departments should be classified so that patients’ access to these basic departments would be facilitated.